The Autoimmune Brain: A Five-Step Plan for Treating Chronic Pain, Depression, Anxiety, Fatigue, and Attention Disorders - Younger, David S. (International Journal of Innovative Research in Medical Science, 2020)
This year, 2019 saw the publication of The Autoimmune Brain1 that explains the background and application of I-Cubed, shorthand for post-infectious immunity and autoimmunity that is closely associated with the causes of common and rare neuropsychiatric illnesses.